ANALISIS PUTUSAN HAKIM NOMOR 373/Pid.Sus/2017/PN.Bnj TERHADAP PENJATUHAN SANKSI PIDNA PADA PELAKU TINDAK PIDANA PENCABULANYANG MENDERITA RETARDASI MENTAL BERDASARKAN HUKUM PIDANA INDONESIA - Muhammad Rafdi; Syaifullah Yophi; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In the Indonesian Criminal Code, there is no clear formulation regarding the abilityto be responsible. Article 44 of the Criminal Code explains the circumstances when a personcannot be sentenced to a criminal sentence because there is an inability to take responsibilityfor the perpetrator of a crime in the form of a mentally disabled or impaired due to illness. Oneexample of the case is contained in the decision Number 373/Pid.Sus/2017/PN.Bnj in thedecision Defendant G who in legal facts was proven to suffer from Moderate MentalRetardation with an IQ of 46. However, in their consideration the Majlis Judge did not considerthe Defendant's Mental Retardation condition G as a determinant of his ability to beresponsible, and stated that Defendant G could be held responsible. So the purpose of thisstudy is to determine the imposition of criminal sanctions on perpetrators of criminal acts ofsexual abuse who suffer from Mental Retardation based on Indonesian criminal law and todetermine the judge's considerations for imposing criminal sanctions for sexual abuse whosuffer from Mental Retardation based on Indonesian criminal law.Application of Article 44 of the Criminal Code on the criminal act of intercourseagainst child in Decision Number 373/Pid.Sus/2017/PN.Bnj is incorrect. Inability to beresponsible for the qualifications of Article 44 of the Criminal Code includes the ability to thinkof the perpetrators of criminal acts. Perpetrator with mental retardation problems withintellectual abilities, which also affects his ability to judge his actions are in accordance withthe rules and values the values that exist in society. The judge's considerations were not carefulin imposing criminal sanctions because several important facts were revealed at the trialregarding the condition of the Defendant. The Majlis Judge should dig deeper into mattersoutside the realm of law that arise from each trial that is presided over and summon experts tothen be asked for the clearest possible explanation in order to decide the case as fairly aspossible.Keywords: Criminal liability, Mental Retardation, Obscenity